Reading Performance of The Grade II Pupils in the Different Teaching Approaches - Mara, Joann T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed determine the level of reading performance of 210 Grade 2 pupils of Sta. Cruz District, Division of Zambales using Marungko Reading Approach and Phonic Reading Approach. The researcher utilized a quantitative descriptive research design and comparative study which helped the researcher collect information that best describe the existing problem by asking respondents of their perceptions about the strategies of teachers in improving the reading preparedness of Grade 2 pupils during modular distance learning. The study revealed that the level of pupils’ reading performance using the Marungko Reading Approach was outstanding while excellent in the use of Phonic Reading Approach was excellent. The level of pupils’ reading difficulty using both the Marungko Reading Approach and the Phonic Reading Approach was very easy. The level of pupils’ reading performance using the Marungko Reading Approach and Phonic Reading Approach has no significant difference. The level of pupils’ reading performance using both the Marungko Reading Approach and the Phonic Reading Approach has significant relationship to their academic performance in English and Filipino. Based on the summary of the investigations conducted and the conclusions arrived at, Teachers use the Marungko Reading Approach and Phonic Reading Approach to improve the reading performance of pupils. Teachers should develop reading program and activities responsive to pupils who are facing difficulty in reading using the Marungko Reading Approach and Phonic Reading Approach. Teachers should seek support from stakeholders for the provision of reading materials appropriate to the garde of pupils. A follow up study may be conducted to validate the results of this research by extending the study in other schools or districts. Teachers should develop reading materials such as strategic intervention material appropriate to the level of pupils using the Marungko Reading Approach and Phonic Reading Approach.